Ultrasound improves the physicochemical and foam properties of whey protein microgel - Wang, Zhaoxin; Zhao, Haibo; Tao, Haiteng; Yu, Bin; Cui, Bo; Wang, Yan (Frontiers in Nutrition, 2023)
Whey protein microgel (WPM) is an emerging multifunctional protein particle and methods to improve its functional properties are continuously being explored. We develop a method to prepare WPM by heat-induced self-assembly under different ultrasound power (160, 320, 480, and 640 W/cm2) and characterize the particle size, surface hydrophobicity, disulfide bond, viscosity, and foam properties of WPM. Ultrasound increased the particle size of WPM-160W to 31 μm. However, the increase in ultrasound power gradually reduced the average particle size of samples. The intrinsic fluorescence spectrum showed that ultrasound unfolded the structure of whey protein and exposed more hydrophobic groups, resulting in increased surface hydrophobicity of WPMs. In addition, infrared spectroscopy suggested ultrasound decreased the α-helix content of WPMs, implying increased flexibility of protein molecules. The disulfide bond of WPMs was broken by ultrasound, and the content of the -SH group increased correspondingly. The rheology indicated that the apparent viscosity decreased with the increase of ultrasonic power. Compared with the control, the ultrasonicated WPMs displayed higher foam ability. Ultrasound improved the foam stability of WPM-160W but destroyed the foam stability of other samples. These results suggest that proper ultrasound treatment can improve the physicochemical and foam properties of WPM.